Synthetic bone mimetic matrix-mediated in situ bone tissue formation through host cell recruitment. (June 2015) - Shih, Yu-Ru; Phadke, Ameya; Yamaguchi, Tomonori; Kang, Heemin; Inoue, Nozomu; Masuda, Koichi; Varghese, Shyni
Graphical abstract: Abstract: Advances in tissue engineering have offered new opportunities to restore anatomically and functionally compromised tissues. Although traditional tissue engineering approaches that utilize biomaterials and cells to create tissue constructs for implantation or biomaterials as a scaffold to deliver cells are promising, strategies that can activate endogenous cells to promote tissue repair are more clinically attractive. Here, we demonstrate that an engineered injectable matrix mimicking a calcium phosphate (CaP)-rich bone-specific microenvironment can recruit endogenous cells to form bone tissues in vivo . Comparison of matrix alone with that of bone marrow-soaked or bFGF-soaked matrix demonstrates similar extent of neo-bone formation and bridging of decorticated transverse processes in a posterolateral lumbar fusion rat model. Synthetic biomaterials that stimulate endogenous cells without the need for biologics to assist tissue repair could circumvent limitations associated with conventional tissue engineering approaches, including ex vivo cell processing and laborious efforts, thereby accelerating the translational aspects of regenerative medicine.